Roles of PAD4 and NETosis in Experimental Atherosclerosis and Arterial Injury: Implications for Superficial Erosion - Franck, Grégory (Circ Res, 2018)
RATIONALE: Neutrophils likely contribute to the thrombotic complications of human atheromata. In particular, neutrophil extracellular traps (NETs) could exacerbate local inflammation and amplify and propagate arterial intimal injury and thrombosis. Peptidyl arginine deiminase 4 (PAD4) participates in NET formation, but understanding of this enzyme’s role in atherothrombosis remains scant. OBJECTIVE: This study tested the hypothesis that PAD4 and NETs influence experimental atherogenesis and in processes implicated in superficial erosion, a form of plaque complication we previously associated with NETs. METHODS AND RESULTS: Bone marrow chimeric Ldlr deficient mice reconstituted with either wild type or Pad4 deficient cells underwent studies that assessed atheroma formation or procedures designed to probe mechanisms related to superficial erosion. PAD4 deficiency neither retarded fatty streak formation nor reduced plaque size or inflammation in bone marrow chimeric mice that consumed an atherogenic diet. In contrast, either PAD4 deficiency in bone marrow-derived cells, or administration of DNaseI to disrupt NETs, decreased the extent of arterial intimal injury in mice with arterial lesions tailored to recapitulate characteristics of human atheroma complicated by erosion. CONCLUSIONS: These results indicate that PAD4 from bone marrow-derived cells and NETs do not influence chronic experimental atherogenesis, but participate causally in acute thrombotic complications of intimal lesions that recapitulate features of superficial erosion.